43-kilodalton glycoprotein from Paracoccidioides brasiliensis: immunochemical reactions with sera from patients with paracoccidioidomycosis, histoplasmosis, or Jorge Lobo's disease. - Puccia, R (1991)
Sera from patients with paracoccidioidomycosis (PCM), histoplasmosis (HP), or Jorge Lobo's disease (JL) were titrated against purified gp43 from Paracoccidioides brasiliensis by using both enzyme-linked immunosorbent assay (ELISA) and immunoprecipitation (IPP) reactions with 125I-labeled antigens. In IPP, PCM sera and other sera could be distinguished on the basis of serum titers, whereas in ELISA, 53% of the HP sera and 29% of the JL sera reacted similarly to the PCM sera. To investigate the possible role of the carbohydrate epitopes in these reactions, we compared the reactivities of sera from several patients with native and deglycosylated gp43. Competition experiments were carried out with monosaccharides as inhibitors. The results suggest that greater than 85% of the reactions of the PCM sera with gp43 involved peptide epitopes. Cross-reactions with HP and JL sera in ELISA were predominantly attributed to periodate-sensitive carbohydrate epitopes containing galactosyl residues. HP and JL sera which reacted strongly with gp43 in ELISA were only weakly reactive or did not react in IPP with labeled antigens in solution. Moreover, ELISA reactions could be significantly inhibited either by monosaccharides or by periodate treatment. Apparently, carbohydrate epitopes in gp43 are more accessible to the antibodies when the molecule is bound to a plastic substrate than when it is in solution. Structural changes in the gp43 antigen arising by N deglycosylation abolish reactivity with PCM sera and support the existence of conformational peptide epitopes.